2010
DOI: 10.1007/s11172-010-0352-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure and charge of Au10 clusters on adsorption of hydrocarbons

Abstract: The interaction of gold clusters Au 10 of different structural and charge states with various hydrocarbons was studied by the PBE density functional method. Saturated hydrocarbons interact weakly with the neutral cluster Au 10 , for charged Au 10 + the alkane-cluster bond energies increase threefold. Unsaturated hydrocarbons interact with cluster surface more strongly than saturated hydrocarbons, while coordination to the benzene ring is possible for aromatic compounds PhC 2 H, PhC 2 H 3 , and PhC 2 H 5 . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Ethane was found to physisorb on an Au(111) surface with a binding energy of 0.25 eV [66], which is in agreement with the theoretical value of 0.22 eV [67]. A similarly weak binding has also been reported for ethane adsorption on small neutral clusters Au x (x = 3-5,10,20) ranging between 0.08 and 0.33 eV [68,69]. The interaction can be considerably enhanced by exchanging one Au atom by a Ni atom [69] or by positively charging the cluster [68].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Ethane was found to physisorb on an Au(111) surface with a binding energy of 0.25 eV [66], which is in agreement with the theoretical value of 0.22 eV [67]. A similarly weak binding has also been reported for ethane adsorption on small neutral clusters Au x (x = 3-5,10,20) ranging between 0.08 and 0.33 eV [68,69]. The interaction can be considerably enhanced by exchanging one Au atom by a Ni atom [69] or by positively charging the cluster [68].…”
Section: Introductionsupporting
confidence: 86%
“…A similarly weak binding has also been reported for ethane adsorption on small neutral clusters Au x (x = 3-5,10,20) ranging between 0.08 and 0.33 eV [68,69]. The interaction can be considerably enhanced by exchanging one Au atom by a Ni atom [69] or by positively charging the cluster [68]. Dehydrogenation has not been reported and is rather unlikely due to the low binding energy.…”
Section: Introductionmentioning
confidence: 56%
“…For over a decade, free clusters have been shown to represent suitable and versatile model systems to mimic the catalytically active sites of heterogeneous catalysts [26][27][28][29][30]. These studies revealed that small neutral and anionic gold clusters preferably bind ethylene in a -like configuration with the exception of the neutral Au atom and the Au 5 cluster [31][32][33][34][35]. The only systematic study on cationic clusters (Au x + , x = 1-10) was reported by Lyalin and Taketsugu showing the preferred adsorption of one C 2 H 4 molecule in a -bonded configuration [31].…”
Section: Introductionmentioning
confidence: 99%
“…33 The catalytic activity of Au/FeO x in CO oxidation is just due to the presence of Au 10 clusters on the surface. Recently, 146,147 we used the Au 10 cluster with the bilayer structure as model in the quantum chemical studies of the adsorption and catalytic properties of gold clusters. The catalytic activity of atomic gold clusters Au n (n = 2, 6 ± 9, 12, 18, 20) supported on MgO in CO oxidation was studied.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of such cationic sites in activation of unsaturated hydrocarbons was predicted theoretically for ligand-free gold clusters. 144,146 Establishment of the mechanism of catalytic selective oxidation of styrene in the presence of gold clusters with certainty requires an additional theoretical research.…”
Section: Viii2 Application Of Au N (Sr) M and Au N (Pr 3 ) M Clustementioning
confidence: 99%